(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Sentiment analysis, one of the research points in the field of natural language processing, has attracted the attention of researchers, and more and more research papers in the field are published. Many literature reviews on sentiment anlaysis, including methods, techniques, and software, have been produced using a variety of research methodologies and tools, but no jurvey has been conducted on the evolution of research methods and topics in sentiment analysis.